“Leales” y “traidores”: La experiencia de disidencia de la Juventud Peronista Lealtad (1973- 1974) - Mariana Pozzoni (Centre de Recherches sur les Mondes Américains, 2013)
Between ends of 1973 and beginning of 1974 the Revolutionary Tendency of the Peronism was crossed by a process of internal dissents that had, as one of his main expressions, the conformation of the Loyalty Peronist Youth. The fracture was accelerated by the murder of José Ignacio Rucci, the general secretary of the CGT, and support of the “Social Pact” promoted by Perón. The murder, allegedly effected by Montoneros, was interpreted by some militants as an unacceptable sample of challenge to the leader. The intention of this article is to analyze the constitution of the group, their militants, their brands and ideas, and the impact that the break had in the most important fronts of the Revolutionary Trend. For it has been repaired specially in the voice of the protagonists, across 27 interviews realized to ex-militants or related of the group. The testimonies allow to recover the perceptions and the own sensations of the actors and realize of the existence of another “heroic story”, that of the "loyalists", who recognizes to the JP Loyalty the virtue of "having saved lives".